Common goods: new forms of participation of civil society in democracy and the economy - Revista de Pensament i Anàlisi, Recerca (RECERCA. Revista de Pensament i Anàlisi, 2014)
Common goods: new forms of participation of civil society in democracy and the economy Bienes comunes: nuevas formas de participación de la sociedad civil en la democracia y la economía Editors: Daniel Pallarés Domínguez and Stefan Eriksson Entire number Número completo